The Pattern of the Early Childhood Soccer Development in TGB Andika Balapulang Club of Tegal district - Amaludin, Apip; Pramono, Harry; Rustiana, Eunika Raffy (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
This is a qualitative study using the survey method, which was located at TGB Andika Balapulang Club, Tegal district with information sources including chairpersons or administrators of clubs, coaches, athletes, talent guides, and trainees' parents. The data was taken using three techniques: interview, observation, documentation. The results were as follows: achievement coaching patterns were said to be good, in each exercise using match simulation patterns, using this survival simulation and attacking simulation made it easy for trainees to face each tournament followed, the training program was categorized as good, because the training program was adapted to the PSSI standard curriculum for Early childhood children and programs were planned according to plan and tiered, funding sources were categorized as Less, funding was still lacking so that parents and communities around often contribute when the role of coach was said to be good, able to motivate students to be enthusiastic in training and be able to achieve, means and enough infrastructure, because some were in accordance with PSSI standards, the role of the board was categorized as good, the management carried out by the management supports the running of the vision and mission of the Club, the parents were very supportive and good community support. Based on the results of the study, it can be concluded that a good coaching process includes all components starting from the management with good management, creative and competent coaches plus material, moral support from trainees' parents and adequate facilities and infrastructure.